2022
DOI: 10.3390/ph15050603
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soloxolone Amides as Potent Anti-Glioblastoma Candidates: Design, Synthesis, In Silico Analysis and Biological Activities In Vitro and In Vivo

Abstract: The modification of natural or semisynthetic triterpenoids with amines can be explored as a promising strategy for improving their pharmacological properties. Here, we report the design and synthesis of 11 novel amide derivatives of soloxolone methyl (SM), a cyano enone-bearing derivative of 18βH-glycyrrhetinic acid. Analysis of their bioactivities in vitro and in silico revealed their high toxicity against a panel of tumor cells (average IC50(24 h) = 3.7 µM) and showed that the formation of amide moieties at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Markov et al showed that U87 cells treated with NAC completely abolished the cytotoxic effect of the new soloxolon amides. This clearly shows that it is dependent on ROS ( Markov et al, 2022 ).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Markov et al showed that U87 cells treated with NAC completely abolished the cytotoxic effect of the new soloxolon amides. This clearly shows that it is dependent on ROS ( Markov et al, 2022 ).…”
Section: Resultsmentioning
confidence: 80%
“…In a study with soloxolone amides, soloxolone tryptamide showed high antiproliferative potential in glioblastoma cells. Soloxolone tryptamide appeared to induce ROS-dependent and autophagy-independent death of U87 and U118 glioblastoma cells via mitochondrial apoptosis ( Markov et al, 2022 ). It has been demonstrated that 18p-glycyretinic acid causes HL60 cells to undergo apoptosis by increasing the generation of reactive oxygen species ( Makino et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that cyanoenone-bearing triterpenoid SM and its derivatives effectively inhibit the proliferation of KELLY and Neuro2a neuroblastoma cells at submicromolar concentrations [17] and exhibit an obvious suppressive effect on a range of metastasis-associated characteristics of tumor cells, such as EMT, motility, invasion, and clonogenicity [17,18,45]. Based on these facts, we decided to explore whether SM affects leptin-mediated processes in Neuro2a cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our research group developed soloxolone methyl (SM), a cyanoenonebearing semisynthetic derivative of glycyrrhetinic acid (Figure 1). This compound was shown to significantly inhibit the viability of NC-derived tumor cells [17] as well as the epithelial-mesenchymal transition (EMT) of melanoma B16 cells and their metastasis in vivo [18]. Considering the revealed antitumor potency of SM and the ability of 2-cyano-3, 12-dioxooleana-1, 9-dien-28-imidazolide (CDDO-Im) (a structural analog of SM; a semisynthetic derivative of oleanolic acid) to prevent body weight gain in high-fat diet-induced obese mice [19], the effect of SM and its analogs on adipokine-induced tumor cells is worthy of detailed investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies in the field of their synthesis, isolation, and antiviral properties have become especially important and timely. Terpene derivatives have been widely used as anticancer drugs, [3][4][5] antimicrobial agents, 6 anti-inflammatory drugs, 7 antiallergic medicines, 8 and antioxidants. 9 Bicyclic derivatives containing camphane, camphor, and pinane structures have demonstrated a wide range of antiviral activities.…”
Section: Introductionmentioning
confidence: 99%